On a superalgebraically converging, numerically stable solving strategy for electromagnetic scattering by impedance cylinders (vol 17, pg 427, 2018) - Sever, Emrah; Tuchkin, Yury A.; Dikmen, Fatih (Springer, 2022)
[No abstract available]